Pattern of hepatobiliary involvement in HIV/AIDS patients: study in a tertiary care centre - Sharma, Kamlesh; Sharma, Vandana; Singh, Aradhana; ., Ketki (International Journal of Research in Medical Sciences, 2018)
Background: Diseases of hepatobiliary system is a major problem in patients with HIV infection. It has been estimated that approximately one third of the death of patients with HIV infection are in some way related to liver disease. While this is predominantly a reflection of the problems encountered in the setting of co-infection Hepatitis B or C, it is also a reflection of the hepatic injury in the form of hepatic steatosis, that can be due to antiretroviral therapy. There had been little work done on liver function tests in HIV patients without pre-existing liver disease like viral hepatitis, or alcoholic hepatitis. So, this study was designed to assess the pattern of liver function test derangement in HIV patients. Aims and objective was to study the different pattern of hepatobiliary involvement in HIV positive patients, and to gauge the extent of liver damage. Methods: The study included 50 HIV positive patients coming to SMS hospital and Medical College, Jaipur, in medicine and HIV clinic of skin and VD department. Subjects having HIV test positive by ELISA, are included in this study. Other causes of liver function derangements were excluded from the study. Results: Maximum number of the patients were in the age group of 23-32 years. Out of 50 cases studied, 41 (82 %) cases had abnormal liver function tests, while 9 (18%) had normal liver function tests. Most of the cases had liver function abnormalities, and most common abnormality was raised SGOT/SGPT. Conclusions: Almost all types of liver function tests are found to be deranged in HIV patients. The pattern of hepatobiliary involvement varied from fatty liver, cholestasis to Toxic necrosis and granulomas.